2016
DOI: 10.1177/1078155215608523
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oncology pharmacist-managed oral anticancer therapy in patients with chronic myelogenous leukemia

Abstract: Our oncology pharmacist-managed oral anticancer therapy program significantly improved TKI adherence rates in CML patients. We attribute the success of our program to consistent follow-up by utilizing routine phone, and secure email follow-ups, that allowed our oncology pharmacists to build a close and trustworthy relationship with patients and families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(137 citation statements)
references
References 17 publications
4
133
0
Order By: Relevance
“…Similar findings have been reported in other chronic disease states where patients appear less likely to adhere to their medication regimen in the absence of symptoms 30. Scheduling regular patient contacts in between clinic visits with a member of the multidisciplinary health care team such as a pharmacist or a nurse so that potential adherence issues could be recognized, discussed, and addressed in a timely manner can be an effective method of improving adherence 12,31…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar findings have been reported in other chronic disease states where patients appear less likely to adhere to their medication regimen in the absence of symptoms 30. Scheduling regular patient contacts in between clinic visits with a member of the multidisciplinary health care team such as a pharmacist or a nurse so that potential adherence issues could be recognized, discussed, and addressed in a timely manner can be an effective method of improving adherence 12,31…”
Section: Discussionsupporting
confidence: 73%
“…A retrospective study in the United States of America found that CML patients on long-term TKI therapy are prone to developing certain medication-related issues such as side effects, drug interactions, and poor accessibility due to out-of-pocket payments 12. Health care providers may not be fully aware of the challenges faced by CML patients in managing their TKI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…While an absence of data regarding the management of these oral chemotherapies exist in the post-HCT maintenance setting, the impact pharmacists can have on the management of oral chemotherapies has been demonstrated in other settings. Lam and Cheung [30] evaluated the impact of an oncology pharmacist-managed oral chemotherapy program for patients with chronic myelogenous leukemia on adherence rate as compared to those managed by usual care. Adherence rate to imatinib therapy was significantly higher in the pharmacistmanaged group versus the usual care group (88.6% vs. 65.8%, respectively; P = .0046) [30].…”
Section: Long-term Carementioning
confidence: 99%
“…Lam and Cheung [30] evaluated the impact of an oncology pharmacist-managed oral chemotherapy program for patients with chronic myelogenous leukemia on adherence rate as compared to those managed by usual care. Adherence rate to imatinib therapy was significantly higher in the pharmacistmanaged group versus the usual care group (88.6% vs. 65.8%, respectively; P = .0046) [30].…”
Section: Long-term Carementioning
confidence: 99%
“…When oral TKIs were introduced, given all their benefits, high adherence rates were a foregone conclusion. However, in their 15 years, adherence rates have been as low as 60% (Noens et al, 2009); other studies have revealed a similar rate of nonadherence of at least 30% (Al-Dewik et al, 2016;Lam & Cheung, 2016;Winn, Keating, & Dusetzina, 2016). Low adherence rates undoubtedly result in unfavorable sequelae (Breccia, Efficace, & Alimena, 2011;Jabbour, Kantarjian, Eliasson, Cornelison, & Marin, 2012;Santoleri et al, 2016;Wu et al, 2010).…”
mentioning
confidence: 99%